The Influence of Hospital Marketing Mix and Consumer Personal Factors on the Selection of Referral Hospitals by Patients - Ira Puspa Rachmawati; Rahmat Bakhtiar; Blego Sedionoto; Ratih Wirapuspita Wisnuwardani; Ratno Adrianto; Hilda Hilda (GLOBAL HEALTH SCIENCE GROUP, 2026)
The selection of referral hospitals is not solely determined by the administrative mechanism of the National Health Insurance (JKN) referral system but is also influenced by hospital marketing strategies and patient characteristics. This study aimed to examine the effects of the hospital marketing mix (7Ps) and personal patient factors on referral hospital selection at Segiri Primary Health Center, Samarinda. A quantitative cross-sectional design was employed involving 348 respondents selected through simple random sampling from 1,758 referred patients. Data were collected using a structured questionnaire that had been tested and confirmed to be valid and reliable. Statistical analyses included Chi-square and Fisher’s exact tests for categorical variables, as well as Kruskal-Wallis and Mann-Whitney tests for non-parametric comparisons. The results indicated that most personal characteristics, including age, gender, education, occupation, income, and JKN ownership, were not significantly associated with referral hospital selection (p>0.05), except for domicile (p<0.05). Clinical factors, represented by the destination polyclinic, showed a strong association with hospital choice (p<0.001). Among the marketing mix components, Product (p=0.026), Process (p=0.018), and Physical Evidence (p<0.0001) significantly influenced referral hospital selection, while Price, Place, Promotion, and People showed no significant effects (p>0.05). In conclusion, referral hospital selection was primarily influenced by service needs and the quality of patient experience rather than personal characteristics. Prioritizing improvements in physical facilities and optimizing service processes are essential to enhance the effectiveness of the referral system.